STORAGE IS THE MOST INFLUENCING FACTOR OF HOSPITAL SOLID WASTE TREATMENT: SEM ANALYSIS - Alhamda, Syukra; Nurmaya, Ika; Hoa , Dinh Thi Phuong (The Indonesian Journal of Public Health, 2025)
Introduction: From primary data, it was found that 65% of solid waste generation occurred in 12 hospitals in West Sumatra. "2,839 health facilities in West Sumatra, produced 1,899.15 tonnes of medical solid waste including hazardous and toxic materials (B3)," the government stated in March 2020. If nothing is done to address this poor waste management, it will negatively affect society. It is difficult for hospital managers to improve the waste processing system because the      stages or factors that have a significant impact on poor waste processing are unknown. Aims: This research aims to find an appropriate medical solid waste treatment model that can be used in hospitals by analyzing the stages and      factors involved in processing medical solid waste. Method: Structural Equation Modeling analysis was used in this cross-sectional research. The population      study was 12 hospitals and the research sample was taken by calculating Wayne      W. Daniel's formula to obtain 120 hospital waste treatment officers. This study started in September 2021 to March 2022. Primary data was collected by writing notes from observations by recording the results of observations, documentation, asking sources, and questionnaires filled out by waste managers and waste cleaning officers. Results: The research results show that of the 4 independent variables      influencing      medical solid waste processing, storage is the most dominant factor affecting waste     processing. Conclusion: Sorting and storage variables influence poor hospital waste management in West Sumatra.